2023
DOI: 10.1001/jamanetworkopen.2023.44457
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Effects of Omnivorous vs Vegan Diets in Identical Twins

Matthew J. Landry,
Catherine P. Ward,
Kristen M. Cunanan
et al.

Abstract: ImportanceIncreasing evidence suggests that, compared with an omnivorous diet, a vegan diet confers potential cardiovascular benefits from improved diet quality (ie, higher consumption of vegetables, legumes, fruits, whole grains, nuts, and seeds).ObjectiveTo compare the effects of a healthy vegan vs healthy omnivorous diet on cardiometabolic measures during an 8-week intervention.Design, Setting, and ParticipantsThis single-center, population-based randomized clinical trial of 22 pairs of twins (N = 44) rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…To investigate the impact of diet on the methylome, blood samples from a randomized clinical trial were used to quantify methylation (Landry et al 2023). As shown in Figure 1 , to quantify methylation, whole blood was collected to establish a baseline measure of methylation at the time of starting the trial (Week 0) and at the conclusion of the study (Week 8).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the impact of diet on the methylome, blood samples from a randomized clinical trial were used to quantify methylation (Landry et al 2023). As shown in Figure 1 , to quantify methylation, whole blood was collected to establish a baseline measure of methylation at the time of starting the trial (Week 0) and at the conclusion of the study (Week 8).…”
Section: Resultsmentioning
confidence: 99%
“…These phytochemicals are also included in beverages, such as teas from tea plants [10,21] and herbal teas. A recent study conducted with healthy identical twins has shown that those who were assigned to consume vegan diet had significantly improved cholesterol concentration, fasting insulin level, and body weight loss compared to those who were assigned to eat omnivorous food, indicating the effects of phytochemicals on several health conditions even among genetically identical twins [34]. The health benefits of fermented foods has also been shown [35][36][37], which not only affect gut microbiota by the probiotic lactic acid bacteria, but also can improve the health status of the person directly by their anti-inflammatory, antioxidant, and other bioactive properties.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of literature that proves the positive impacts of dietary changes to more plant-based diets, as suggested by the EAT-Lancet Commission [ 6 , 7 , 8 , 9 ]. For example, a Swedish study concluded that a high accordance of the individual diet with the PHD was associated with a 25% decreased mortality risk [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a Swedish study concluded that a high accordance of the individual diet with the PHD was associated with a 25% decreased mortality risk [ 7 ]. In a recent study, Landry et al [ 9 ] showed beneficial cardiometabolic effects of plant-based vs omnivorous diets in identical twins. Springmann et al [ 8 ] analyzed the health and environmental impacts of different diet scenarios for selected regions in the world and showed that in high-income countries, the change to more plant-based diets, as recommended by the PHD, would lead to improved nutrient levels, a reduced risk of premature death, and the reduction of environmental impacts.…”
Section: Introductionmentioning
confidence: 99%